Design of ultra wideband slotted microstrip patch antenna - Ping L.C.; Chakrabarty C.K.; Khan R.A. (2023)
In this paper, the design of an Ultra Wideband slotted microstrip patch antenna is presented. The proposed antenna has good performance of UWB with impedance bandwidth between 1.78 GHz to 11.13 GHz. The antenna exhibits the return loss (S11) below -10 dB for the frequency range mentioned. Effects of design antenna parameters such as the slot (size, position and dimension), patch shape and feed width have been investigated to obtain a better S11 value. Results are obtained using CST Microwave Studio. 2009 IEEE.